2016
DOI: 10.1002/jbm.a.35795
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced osteoprogenitor elongated collagen fiber matrix formation by bioactive glass ionic silicon dependent on Sp7 (osterix) transcription

Abstract: Bioactive glasses release ions, those enhance osteoblast collagen matrix synthesis and osteogenic marker expression during bone healing. Collagen matrix density and osteogenic marker expression depend on osteogenic transcription factors, (e.g., Osterix (OSX)). We hypothesize that enhanced expression and formation of collagen by Si(4+) depends on enhanced expression of OSX transcription. Experimental bioactive glass (6P53-b) and commercial Bioglass(TM) (45S5) were dissolved in basal medium to make glass conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…In addition, IGF1 is involved in the activation of β-catenin [ 54 , 55 , 56 ], generating a positive feedback circuit that contributes to the proliferation, migration, and survival of endothelial cells [ 24 , 25 , 26 , 27 ]. On the other hand, it is important to point out that Si and Li + ions also promote osteogenesis and bone repair [ 18 , 19 , 50 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. It would be therefore of interest to further evaluate the angiogenic and osteogenic effects of 45S5.5Li particles of different sizes (nano- and micrometric) and/or scaffolds derived from the bioactive glass 45S5.5Li by using more complex cell cultures such as the co-culture of osteoblasts with endothelial cells, as well as in experimental models of bone repair in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, IGF1 is involved in the activation of β-catenin [ 54 , 55 , 56 ], generating a positive feedback circuit that contributes to the proliferation, migration, and survival of endothelial cells [ 24 , 25 , 26 , 27 ]. On the other hand, it is important to point out that Si and Li + ions also promote osteogenesis and bone repair [ 18 , 19 , 50 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. It would be therefore of interest to further evaluate the angiogenic and osteogenic effects of 45S5.5Li particles of different sizes (nano- and micrometric) and/or scaffolds derived from the bioactive glass 45S5.5Li by using more complex cell cultures such as the co-culture of osteoblasts with endothelial cells, as well as in experimental models of bone repair in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Osterix, a zinc finger transcription factor, is widely accepted as a master osteogenic factor. The essential role of osterix in osteogenesis relies on its ability to regulate the expression of a number of osteoblast markers, such as osteopontin, Dkk1, and collagen type I. The above results have confirmed that the piezoelectric effect can effectively promote the upregulation of osterix gene expression. Therefore, our study further clarifies the mechanism of osterix upregulation.…”
Section: Discussionmentioning
confidence: 71%
“…This amplied OSX expression may be associated with the presence of an increased glassy phase (Si) and enhanced Ca dissolution in HB 30 S. This was supported by a previous nding, where commercial Bioglass™ (45S5)-conditioned media signicantly induced OSX and osteogenic differentiation of the MC3T3-E1 calvaria cell line. 73…”
Section: Osteogenic Intra-and Extra-cellular Proteinsmentioning
confidence: 99%